Feasibility and sustainability of a nurse-led intervention to integrate HPV vaccination into medical processing for active-duty Soldiers - Emily Penick; Brigid K. Grabert; Emma Stockton; Hannah Prentice-Dunn; Marion Ward; Trinita Kirk; Melissa B. Gilkey (Taylor & Francis Group, 2022)
To increase Soldiers' access to HPV vaccination, we evaluated the feasibility and sustainability of a nurse-led intervention to integrate HPV vaccination into medical processing procedures for Soldiers. We partnered with nursing staff to introduce HPV vaccine into existing vaccination services at a nurse-led clinic that serves Soldiers at Fort Bragg, North Carolina. In addition to stocking the vaccine, the intervention included training nursing staff (n = 11) strategies for recommending HPV vaccination for Soldiers ages 18-26. We conducted surveys of nursing staff to assess their perspectives on feasibility. Nursing staff tracked HPV vaccine uptake among Soldiers for 4 weeks post-training to assess adoption and again for 2 weeks at 4-month follow-up to assess sustainability. We assessed delivery cost as the cost of personnel time, vaccine doses, and other materials during the initial 4-week intervention period. Nursing staff agreed that recommending HPV vaccination fit in with medical processing procedures (mean = 4.6 of 5.0). Of the 516 Soldiers offered HPV vaccine in the 4 weeks following the training, 198 (38%) accepted and received the vaccine. Soldier ages 18-20 more often accepted HPV vaccination than older Soldier ages 21-26 (46% versus 32%, p < .01). Vaccine uptake was similar at follow-up, with 98 of 230 eligible Soldiers (43%) receiving HPV vaccine. The total delivery cost was $12,737, with an average cost per vaccine dose delivered of $64. Our findings suggest that training nursing staff to recommend and administer HPV vaccinations to Soldiers is feasible and warrants wider-scale testing as a strategy to protect soldiers from HPV-attributable cancers.